Designing 'Aku yang Bersinar' Illustration Book as an Educational Media for Teenage Self-Confidence - Aris Sutejo; Atraba, Harin (Universitas Ciputra, 2024)
Adolescence is a transitional period from childhood to adulthood. Due to this condition, adolescent development is also followed by other developmental tasks. If adolescents fail to carry out their developmental tasks, it will have negative consequences in social life in the following phases. The role of parental care is very influential on the nature and behavior of adolescents, good parenting forms traits that are confident, take initiative, have ambition, have normal emotions, are responsible, and are able to carry out positive interpersonal ties. The lack of full parenting in the Child Social Welfare Institution (LKSA) or orphanage makes adolescents have a negative self-concept, one of which is the low character of self-confidence. This design aims to create learning media in the form of illustration books that provide education on self-confidence in adolescents, learning to know the strengths and weaknesses of individuals so as to prepare orphanage adolescents to become part of society. The methods used in this design are quantitative and qualitative. The result of the design is a printed book entitled 'Aku yang Bersinar'.